Analysis of the Determinants of Exercise Habits, Diet, and Heredity History with the Incidence of DM in Productive Age at Tirto 1 Health Center, Pekalongan Regency, Indonesia - Anisah Maulida; RM, Dewi Nugraheni; Aris Santjaka (HM Publisher, 2023)
Degenerative disease in the form of diabetes mellitus which spreads to the elderly because there is a decrease in the function of the body's organs. The industrial revolution 4.0 affects diet and lifestyles which are estimated to increase the risk of diabetes mellitus in productive age. This study aimed to determine the relationship between exercise habits, diet and hereditary history with the incidence of diabetes mellitus in productive age. The research was carried out in April - May 2023 on 51 respondents each with analysis techniques using the Chi – square test and logistic regression. The results of the study showed that there was no relationship between exercise habits (p =0.269, OR=3.267), there is a relationship between diet based on food ingredients including the variable carbohydrate consumption habits (p =0.001, OR = 6.3), and soft drinks (p = 0.031, OR = 5.976) which is a risk factor. While animal protein (p= 0.001, OR=0.001), vegetables (p=0.003, OR = 0.17), fruits (p= 0.003, OR = 0.26) is a protective factor. The results of the analysis of food ingredients that did not show any relationship with the incidence of diabetes mellitus (DM) in productive age included vegetable protein (p = 1,000, OR = 1,000), dairy (p = 1,000, OR=1,000), nuts (p = 0.454, OR=1.654) and snacks (p = 0.523, OR = 1.87) as well as family history (p = 0.029, OR=2.636). Apart from that, it was found that there was a relationship between hereditary factors and the incidence of DM in productive age and became a risk factor in the research. In conclusion, protein is the most dominant influencing variable and protective factor in this research.